Образно-стильова палітра сучасного акровіршування - Науменко, Наталія; Naumenko, Nataliia (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про специфіку популяризації поетичних творів, зокрема курйозних віршів, через мережу Інтернет. Показано особливості російськомовного акровіршування, яке в молодіжних колах користується значним попитом, та перспективи розвитку україномовного акровірша, до якого, завдяки спілкуванню на форумах, долучається дедалі більше людей різного віку. The article deals with the specific features of popularizing the verse works, particularly those curious (like palindromes, acrostics etc.), through Internet. There were hjghlighted the properties of Russian language acrostics, that evoke great interest in youth, and their genre peculiarities in poetic works by anonymous authors, represented on various literary websites. There were also outlined the perspectives of development of Ukrainian acrostic that is now being created by more people of different age, thanks to communication on Internet forums. Particularly, the author of this article has confirmed that, just similarly to Baroque traditions, any individual acrostic may be as well an iconic reflection of the poet oneself and the unique emblematic literary work (a present to the holiday, a ‘visiting card’ etc.). Besides, there was also established the role of acrostic writing, as a creative task, in the secondary school teaching practice, which is stimulating the students to cognize the semantics of a letter as the initial of the language, and its possible transformations.
Image and Style Diversity of Contemporary Acrostic Writing
Keywords: поезія; курйозне віршування; жанр; акровірш; Інтернет; poetry; curious versification; genre; acrostic; Internet